Antioxidant and Antimicrobial Activities of (‐)‐Epigallocatechin‐3‐gallate (EGCG) and its Potential to Preserve the Quality and Safety of Foods. Issue 3 (16th April 2018) - Nikoo, Mehdi; Regenstein, Joe M.; Ahmadi Gavlighi, Hassan
Abstract: Quality deterioration of fresh or processed foods is a major challenge for the food industry not only due to economic losses but also due to the risks associated with spoiled foods resulting, for example, from toxic compounds. On the other hand, there are increasing limitations on the application of synthetic preservatives such as antioxidants in foods because of their potential links to human health risks. With the new concept of functional ingredients and the development of the functional foods market, and the desire for a "clean" label, recent research has focused on finding safe additives with multifunctional effects to ensure food safety and quality. (‐)‐Epigallocatechin‐3‐gallate (EGCG), a biologically active compound in green tea, has received considerable attention in recent years and is considered a potential alternative to synthetic food additives. EGCG has been shown to prevent the growth of different Gram‐positive and Gram‐negative bacteria responsible for food spoilage while showing antioxidant activity in food systems. This review focuses on recent findings related to EGCG separation techniques, modification of its structure, mechanisms of antioxidant and antimicrobial activities, and applications in preserving the quality and safety of foods.